Students Perception on the Use of Blooket for Vocabulary Mastery - Artanti Callista Raihan; Putu Dian Danayanti Degeng (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study investigates students’ perceptions of using Blooket, a web-based game platform, for English vocabulary mastery. Employing a mixed-method design, the study collected quantitative data from 29 students at SMAS Widyagama through a nine-item Likert-scale questionnaire, and qualitative data through semi-structured interviews with five students. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis following Braun and Clarke’s (2006) six-phase framework. The findings indicate that students hold an overall positive perception of Blooket with mean = 3.68, Agree. The highest-rated aspect was students’ interest due to game variety, driven primarily by competitive ranking and scoring mechanics. Qualitative findings confirmed and enriched the quantitative results, revealing that neutral questionnaire responses were attributable to three non-substantive factors: memory lapse, limited English proficiency, and rushed questionnaire completion. Additionally, Blooket is most effective when used as a post-instruction reinforcement activity. These results suggest that game-based learning tools can positively enhance student engagement and vocabulary learning when implemented appropriately.